THE EFFECT OF STRATEGIC LEADERSHIP, GOOD CORPORATE GOVERNANCE, AND OPEN INNOVATION ON FAMILY BUSINESS SUSTAINABILITY IN JAVA ISLAND WITH SUSTAINABLE COMPETITIVE ADVANTAGE AS AN INTERVENING VARIABLE - Antoni, Rio; Kurniawan, Daniel (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
This research aim for analyze the effect of strategic leadership, good corporate governance, and open innovation on the sustainability of family businesses on the island of Java with sustainable competitive advantage as intervening variables. This research use method quantitative with the primary data collected through questionnaire to 260 family businesses on the island of Java. Data analysis techniques used is PLS (Partial Least Squares). The results of the research show that strategic leadership and good corporate governance have an influence positive and significant towards the sustainability of family businesses. Open innovation also has an impact positive and significant towards the sustainability of family businesses, but its influence can also be mediated by sustainable competitive advantage. Sustainable competitive advantage is proven capable mediate The influence of open innovation on family business sustainability. This research give implications important for family business leaders on the island of Java. Family business leaders need implementing strategic leadership and good corporate governance to increasing the sustainability of family businesses. Open innovation can also implemented For improve the sustainability of family businesses, but need noticed that sustainable competitive advantage is variables important mediator​ The influence of open innovation on family business sustainability. Competitive Advantage.